Pengaruh Kualitas Pelayanan, Kualitas Produk dan Harga Terhadap Kepuasan Pelanggan Serta Dampaknya Pada Loyalitas Pelanggan Hotel X di Jakarta - Rita Mardiana (Peneliti.net, 2022)
The phenomenon of customer satisfaction at Hotel X in Jakarta is not yet optimal. The purpose of this study is to analyze the effect of service quality, product quality, and price on customer satisfaction and its impact on customer loyalty at Hotel X in Jakarta, directly or indirectly. The data analysis used the path analysis method with the research population being visitors to Hotel X in 2015 with a total of 14,825 customers and with the Slovin formula (10%) obtained 100 samples. The results of the path analysis measurement show that there is a positive direct and indirect effect of service quality, product quality, and price on customer satisfaction and its impact on customer loyalty at Hotel X in Jakarta.